EAWE: Examination of Anomalous World Experience - Sass, Louis Arnorsson; Pienkos, Elizabeth; Stanghellini, Giovanni; Fuchs, Thomas; Parnas, Josef (Psychopathology, 2017)
The “EAWE: Examination of Anomalous World Experience” is a detailed semi-structured interview format whose aim is to elicit description and discussion of a person's experience of various aspects of their lived world. The instrument is grounded in the tradition of phenomenological psychopathology and aims to explore, in a qualitatively rich manner, six key dimensions of subjectivity - namely, a person's experience of: (1) Space and objects, (2) Time and events, (3) Other persons, (4) Language (whether spoken or written), (5) Atmosphere (overall sense of reality, familiarity, vitality, meaning, or relevance), and (6) Existential orientation (values, attitudes, and worldviews). The EAWE is based on and primarily directed toward experiences thought to be common in, and sometimes distinctive of, schizophrenia spectrum conditions. It can, however, also be used to investigate anomalies of world experience in other populations. After a theoretical and methodological introduction, the EAWE lists 75 specific items, often with subtypes, in its six domains, together with illustrative quotations from patients. The EAWE appears in a special issue of Psychopathology that also contains an orienting preface (where the difficulty as well as necessity of studying subjective life is acknowledged) and a brief reliability report. Also included are six ancillary or background articles, which survey phenomenologically oriented theory, research, and clinical lore relevant to the six experiential domains.